Reliability of mpMRI in diagnosing cancer prostate following intravesical BCG for bladder cancer - Arjun Pon Avudaiappan; Pushan Prabhakar; Rachel Siretskiy; Andrew Renshaw; Ahmed Eldefrawy; Murugesan Manoharan (BJUI Compass)
Abstract Background Detecting carcinoma prostate (CaP) after intravesical Bacillus Calmette Guerin (BCG) immunotherapy for non‐muscle invasive bladder cancer (NMIBC) poses diagnostic challenges. Granulomatous prostatitis (GP) has an incidence of 0.8%–3.3% in post‐intravesical BCG patients and 6% incidence in a PIRADS 5 lesion on multiparametric MRI (mpMRI). Patients with GP after intravesical BCG may have clinical, biochemical, and radiological features similar to CaP. In our study, we evaluate the reliability of mpMRI in diagnosing CaP after intravesical BCG therapy. Materials and Methods We reviewed the NMIBC patients treated with intravesical BCG therapy between 2017 and 2023 and investigated those who underwent mpMRI and MR fusion biopsy in suspicion of CaP. A total of 120 patients had intravesical BCG immunotherapy, and 10 patients met our selection criteria. We performed a descriptive analysis of these patients and assessed the sensitivity and specificity of mpMRI in diagnosing CaP. Results The sensitivity of mpMRI in detecting CaP was 100%, and the specificity was 28.6%. Similarly, the negative predictive value for detecting CaP was 100%, and the positive predictive value was 37.5%. Among patients evaluated with mpMRI, a PIRADS 4 or 5 lesion was seen in 8 (80%) patients, and there was no lesion in 2 (20%) patients. The mpMRI detected 1 lesion in 6 patients (60%) and 2 (20%) in 2 patients. The lesions had a PIRADS score of 4 and 5 in 6 (60%) and 2 (20%) patients, respectively. Among these lesions, 8 (80%) were in the peripheral zone and 2 (20%) in the transition zone. In the MR fusion biopsy of these 10 patients, 7 (70%) had granulomatous prostatitis, and 3 (30%) had CaP. Conclusion In our study on evaluating the reliability of mpMRI in diagnosing CaP among post‐intravesical BCG patients, we noted that although PIRADS in mpMRI had high sensitivity in identifying prostate lesions, its specificity for detecting CaP is limited.